OP0211 Reprogramming of Metabolic Pathways Inhibits TLR2-Induced Inflammation in RA. (15th July 2016) - Mcgarry, T.; Biniecka, M.; Veale, D.; Fearon, U.
Abstract : Background: Recent studies have emphasized a tight link between the metabolic state and phenotype of immune/inflammatory cells. Metabolic turnover of the inflamed synovium may induce a cellular switch in energy production, characterised by a glycolytic flux, suppression of mitochondrial function and potentiation of inflammation. The role of Toll-like receptors (TLRs) in immune responses is well documented, however emerging evidence suggests they also play a role in metabolism. Objectives: In this study, we examine mitochondrial function, cellular metabolism and synovial inflammation in response to TLR2 activation. Methods: RA synovial explant cultures and RA synovial fibroblasts (RASFC) were cultured with TLR2-ligand Pam3CSK4 (1μg/ml). Mitochondria DNA (mtDNA) mutations were assessed using a Random Mutation Capture assay and reactive oxygen species (ROS), mitochondrial membrane potential (MMP) and ATP levels were quantified using fluorescent probes. Mitochondrial and glucose metabolism gene arrays were quantified by RT-PCR and the mitochondrial ultrastructure assessed by transmission electron microscopy (TEM). Surrogate markers of glycolysis PKM2, GLUT1, ATP5B and GAPDH were quantified in RA/OA synovium by immunohistochemistry. PKM2 was also assessed by western blotting and immunofluorescence. Finally, we examined the effect of glycolytic inhibitor 3-(3-pyridinyl)-1-(4-pyridinyl)-2-propen-1-one (3PO) (20μM) on TLR2–induced cytokine production, invasion/migration and signalling components NFκBp65, Notch-1IC and p-STAT3. Results: Pam3CSK4 significantly induced mtDNA mutation frequency, ROS, and inhibited the MMP. In parallel, Pam3CSK4 differentially regulated key mitochondrial genes SOD2, BNIP3 and BBC3 (all p<0.05) and markedly altered the ultrastructure of mitochondria. Consistent with this, we demonstrated altered metabolic activity in RASFC, with induced PKM2 nuclear translocation, increased ATP levels and differential regulation of metabolic genes FBP1/2, PGAM2 and ACo2 (all p<0.05), resulting in metabolic shift in favour of glycolysis. This change in metabolic activity was mirrored in-vivo where expression of PKM2, GLUT1 and ATP5B were significantly higher in RA synovium compared to OA (p<0.05). Finally, reprogramming of metabolism using 3PO significantly inhibited TLR2-induced cytokine production, cell migration/invasion and transcriptional regulation of NFκBp65 and p-STAT3. Conclusions: Reprogramming of metabolic activity in RA resulted in resolution of inflammation. These results show close interactions between innate immunity, metabolism and inflammation, further elucidation of these interactions may provide new insights to new therapeutic approaches in RA. Disclosure of Interest: None declared